Quality assurance of carbon ion and proton beams: A feasibility study for using the 2D MatriXX detector. Issue 6 (June 2016) - Varasteh Anvar, M.; Attili, A.; Ciocca, M.; Donetti, M.; Fanola Guarachi, L.K.; Fausti, F.; Giordanengo, S.; Marchetto, F.; Molinelli, S.; Monaco, V.; Sacchi, R.; Vignati, A.; et al.
Highlights: The MatriXX detector is proposed for daily quality assurance in scanned ion beam therapy centers. The detector was tested with proton and carbon ion beams. Good sensitivity for beam position and field uniformity measurements was achieved. Abstract: Purpose: The quality assurance (QA) procedures in particle therapy centers with active beam scanning make extensive use of films, which do not provide immediate results. The purpose of this work is to verify whether the 2D MatriXX detector by IBA Dosimetry has enough sensitivity to replace films in some of the measurements. Methods: MatriXX is a commercial detector composed of 32 × 32 parallel plate ionization chambers designed for pre-treatment dose verification in conventional radiation therapy. The detector and GAFCHROMIC® films were exposed simultaneously to a 131.44 MeV proton and a 221.45 MeV/u carbon-ion therapeutic beam at the CNAO therapy center of Pavia – Italy, and the results were analyzed and compared. Results: The sensitivity MatriXX on the beam position, beam width and field flatness was investigated. For the first two quantities, a method for correcting systematic uncertainties, dependent on the beam size, was developed allowing to achieve a position resolution equal to 230 μm for carbon ions and less than 100 μm for protons. The beam size and the field flatness measured using MatriXX were compared with the same quantities measured with the irradiated film, showing a good agreement. Conclusions: The results indicate that a 2D detector such as MatriXX can be used to measure several parameters of a scanned ion beam quickly and precisely and suggest that the QA would benefit from a new protocol where the MatriXX detector is added to the existing systems.